(untitled) (Bangladesh Journal of Botany, 2015)
Diversities in the pollinia morphology of the family Asclepiadaceae in respect to pollinium shape, size, color, length and breadth of pollinial sac, length and breadth of corpusculum and length and breadth of caudicle were studied in 13 species belonging to eight genera (Cynanchum L., Calotropis R.Br., Glossonema Decaisne., Leptadenia R.Br., Pergularia L., Sarcostemma R.Br., Tylophora R.Br and Vincetoxicum N. M. von Wolf.) Calotropis procera (Ait.) Ait. f. yielded largest pollinia sac. (906.4 4.4.7 ?m) whilst the smaller one (109.8 × 48.0 ?m) was represented by Cynanchum pollens Hemsley and Lace. In respect of the length and breadth of the corspuseulem, C. Procera yielded the lowest one bt Leptodaenia pyrotechnium yielded the smallest (65.2 × 41.2 ?m). DOI: http://dx.doi.org/10.3329/bjb.v43i3.21590 Bangladesh J. Bot. 43(3): 249-253, 2014 (December)